Peningkatan Kompetensi Mitigasi Bencana Siswa Dengan Implementasi Pendekatan Bencana Dalam Perspektif Islam - Dewi Hidayati (STAI Syaichona Moh. Cholil Bangkalan, 2018)
To prepare a community that is ready and alert to natural disasters needs to be instilled and introduced early to the students in the context of education how Islam sees disaster. During this time, students are of the view that Islamic values, have not touched on disaster and disaster mitigation because of their ignorance about the teachings of Islam itself. Usually they also know superficially, without going through an in-depth study of the Islamic view of the damage to the environment and the disaster itself. For that, it needs to be introduced in more depth about the Islamic view of disaster. The approach of this research is quantitative research with comparative design. The subject of this research is the students of State Junior High School located in Bangkalan District, with stratification of city, middle, and periphery schools. In this study used questionnaire method to know the initial description of students' knowledge about disaster theology approach in Islamic perspective and to know the competence of disaster mitigation attitude and skill aspects. Data analysis in this research is used T Test Indenpendent Samples Test with SPSS 20. The result of this research shows that most students have good knowledge about disaster and disaster mitigation in Islamic perspective. There is a difference in disaster mitigation competencies in attitude and skill aspects between the implementation of disaster theology approach in Islamic perspective with material-based approach to students of State Junior High School (SMPN) in Bangkalan District.